Practical data science cookbook : 89 hands-on recipes to help you complete real-world data science projects in R and Python /: 89 hands-on recipes to help you complete real-world data science projects in R and Python. (2014) - Ojeda, Tony; Murphy, Sean Patrick; Bengfort, Benjamin; Dasgupta, Abhijit
No abstract available